2008
DOI: 10.1080/10629360701843318
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of the enzyme Catechol-O-Methyltransferase: methodological issues

Abstract: Results from extensive 70 ns all-atom molecular dynamics simulations of catechol-Omethyltransferase (COMT) enzyme are reported. The simulations were performed with explicit TIP3P water and Mg 2þ ions. Four different crystal structures of COMT, with and without different ligands, were used. These simulations are among the most extensive of their kind and as such served as a stability test for such simulations. On the methodological side we found that the initial energy minimization procedure may be a crucial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, the ligand recognition residues moved significantly, suggesting that ligand-binding loops alter their structure for various sizes of ligands. Recently, an MD simulation structure of rat S-COMT (Bunker et al, 2008) showed that the position of each helix and sheet determined from the crystal structure of the Apo enzyme adopted almost the same position as that of the Holo and quaternary complex structures. However, the relative position of helixes and sheets determined from a 70 ns MD simulation structure was quite different from that of Apo structure; hydrogen bond-mediated helix-helix, helix-sheet, and sheet-sheet interactions might have been broken under the energy minimization steps and loosened the overall structure.…”
Section: Overall Structurementioning
confidence: 99%
“…However, the ligand recognition residues moved significantly, suggesting that ligand-binding loops alter their structure for various sizes of ligands. Recently, an MD simulation structure of rat S-COMT (Bunker et al, 2008) showed that the position of each helix and sheet determined from the crystal structure of the Apo enzyme adopted almost the same position as that of the Holo and quaternary complex structures. However, the relative position of helixes and sheets determined from a 70 ns MD simulation structure was quite different from that of Apo structure; hydrogen bond-mediated helix-helix, helix-sheet, and sheet-sheet interactions might have been broken under the energy minimization steps and loosened the overall structure.…”
Section: Overall Structurementioning
confidence: 99%
“…Despite many pharmacological and clinical studies, we are unaware of any prior computational study of nebivolol. Related atomic-level MD simulations of ligand docking have been performed for other systems such as catechol-O-methyltransfrase 17 and prolyl oligopeptidase. 18 In this paper we combine use of both molecular docking and atomistic classical MD simulations to explore the different binding modes of srrr-and ssss-nebivolol (the least active form of the drug) in the binding site of β 2 AR.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Although RESP charges are available for nicotinamide cofactors, modern automated pipelines were found to produce reliable parameters for all major force fields. [162][163] Optimized S-adenosyl-methionine (SAM) parameters have been published for various force fields, [164][165] and PLP RESP charges are available for AMBER. [166] Parameterization of flavins requires extra care because the electron density in the central three-ring structure cannot easily be fragmented into smaller groups.…”
Section: Optimized Parameters For Non-proteogenic Partsmentioning
confidence: 99%